-
Since their difference is constant, let's do the difference first and see what it is.
That is: 3x*2+my-8-(-n*2+2y+7)=(3+n)x*2+(m-2)y-15=c(c represents constant).
From the equality of polynomials, 3+n=0 and m-2=0 are obtained
So n=-3, m=2, and then n*m+mn=(-3)*2-6=3
-
The difference between the two formulas is 3x2+my-8-(-nx2+2y+7)=(3+n)x+(m-2)y-15
Since it is a constant, then the x-y coefficient is zero: 3+n=0 m-2=0n=-3 m=2
nm+mn=3
-
The coefficients of the two equations x and y terms are equal.
So, n=-3, m=2
mn+nm=-12
-
Subtract the two polynomials to get (3+n)x+(m-2)y-1 Since it is a constant, then the x-y coefficient is zero, 3+n=0, m-2=0, okay, and then it is solved.
-
The coefficients of the two equations x and y terms are equal, so, n=-3, m=2, the required value, solve it yourself.
-
Subtract by equation 2, and the coefficients of x and y are 0. Isn't it going to be done??
-
The exposed part is from 4 to 8, the water surface drops by 1, then continue to pull out every 4 to reduce 1, and the water surface can be pulled 9 times to restore to the original height, then the column height is 8 + 4 * 9 = 44
Calculated volume 7 square *44=
-
When v=s*h stones are vertically exposed to the water surface for 4 cm, the water level in the tank rises by 10 cm.
V Stone Underwater = S Stone * (H Stone - 4) = S Tank * 10 When the stone is vertically exposed to the water surface for 8 cm, the water surface in the tank drops by 1 cm.
The volume of 1 cm falling from the surface of the water is equal to the volume of the stone rising by 4 cm (8-4 = 4) s trough = 4s stone
Substitution: H stone = 44 cm.
V-stone = *7*7*44=2156 cubic centimeters.
-
Forehead... Was it that I was thinking too simply?
When the water is exposed vertically for 4 cm, the rest is in the water and is the same volume as the rising 10 cm of water.
At this time, pull out another 4cm, that is, when there is 8cm on the water surface, the water surface will drop 1cm on the basis of the original rise
Because the cylindrical stone is placed vertically, the volume of water that is 1 cm high is the volume of the pillar of 4 cm.
When the stone is completely pulled out of the water, the surface of the water will return to its original beginning. The height of the stone is not 10*4+4=44cm
The bottom radius is also known, doesn't it come out?
It seems that the equation is not used...
-
The height of the cylinder is.
The volume of the cylinder.
v=π×7×7×44
The reason is as follows: the exposed part of the cylinder is from 4 cm to 8 cm, and the water surface drops from 10 cm to 9 cm, which is a regular decline, (this is the key point to seek height, it is an implied relationship, pay attention to it) The cylinder rises 9 times, but it has been completely pulled out. The height of the cylinder can be found, the radius has been given, and the volume can be found.
-
The water level in the sink drops by 1 cm? Are you sure it's a drop? Isn't it supposed to go up.
Will it be a rise of 1cm. Press the rise of 1cm and the answer is as follows:
Set the bottom area of the sink to be s. The height of the stone is xcm.
7·7·(x-4) s·10,·7·7· (x-8) Divide the two equations of s·1 to give x=76 9
The volume of the stone is ·7·7·76 9=......
-
Solution: Let the bottom area of the cuboid be x cubic centimeters and the height of the cylinder be y centimeters.
10x=π×7²×(y-4)
10-1)x=π×7²×(y-8)
The solution is x=y=44
It is known that the height of the cylinder is 44, so the volume of the cylinder is.
7 44 = 2156 cubic centimeters.
So the volume of the cylinder is 2156 cubic centimeters.
-
Solution: Let the height of the stone be h cm and the base area of the cuboid be s, then.
h-4)×49π=10s ①
h-8)×49π=9s ②
The solution of the two formulas can be obtained: h=44
Then the volume of the stone is v=44 49=2156.
I guess so.
-
Think of it as a 10 cm rise and 1 cm drop!
Let the volume of the stone be x cubic centimeters.
x-7*7*pie*4) 10=(x-7*7*pie*8) (10-1)Equivalence relation: The bottom area of the water contained in the sink is equal.
The rest is omitted.
-
Solution: There are a total of x sons and y family property.
Since each son has the same amount, select the first two sons, and you can list:
100+10%*(y-100)=200+[y-100-10%*(y-100)-200]*10%
y=8100
The first son is divided into 100 + (8100-100) * 10% = 900, so x = 8100 900 = 9
-
Solution: Set up a family property with x dollars.
The first son's points: 100 + (x-100) 10% = the rest after the first son's points;
The second son is divided: 200+ (
As a result, each son gets the same amount:
x=8100
Cents per son: dollars).
There are a total of sons: 8100 900 = 9 (one).
-
The first question, if the property is X yuan, then the property relationship between the eldest son and the second son is:
100+x*10%=200+(x-x*10%)*10%100+
The property obtained is: x=10000
-
Solution: Set up a family property with x dollars.
100+ from the title
The solution is x=8100
Cents per son: dollars).
So there are a total of sons: 8100 900 = 9 (pcs) This question is very familiar, like a question in our textbook.
-
1) Set A and B to meet in x hours.
72x+48x=360
x = 3 (2) The vehicle has been driven for x hours.
72x+48x=360+100
x=(3) Let car B meet after X hours of departure.
72*(25/60)+72x+48x=360x=
-
The time it takes for two cars to meet.
360-25 60*72) (72+48)+25 60=19 6 (hours).
The time it takes for the two cars to be 100km apart after the encounter.
100 (48+72) = 5 6 (hours).
Total time: 19 6 + 5 6 = 4 (hours).
-
Idea: It is easy to solve the problem by treating a and b as x and y as a whole.
Solution: Let a = x and b = y
Yes: 3x-4y=5 2x+3y=10 solution x=55 17 y=20 17 substitution.
1, -15x+3y=-45
2, 2x-14y=-10
-
3a²-4b²=5,2a²+3b²=10
Solving these two systems of equations is sufficient.
a²=55/17
b²=20/17
Then you can substitute it in.
-
a -4b = 5, 2a + 3b = 10, and the two are added to give 5a —b = 15, and the resulting equation is multiplied by -3 to get the value of -15a +3b as -45
a -4b = 5, 2a +3b = 10, subtract the two to get a -7b =—5, and multiply the equation by 2 to get the value of 2a -14b is -10
-
1991+8009=10000
So the last four digits of 1990 to the nth power are 0000
10000 is 10 to the 4th power.
So n min = 4
Take the "six" in the ten place as "nine", and the "three" in the unit position as "five", that is, take 63 as 95, and calculate 97, so 95-(-2) = 97, so 63-(-2) = 65, and finally 65
The result is 31, and from the four known figures, the circle, square, and triangle each represent three numbers. And the position of the two figures in each diagram represents a certain addition and subtraction relationship. >>>More
c. Obtuse triangle.
Angle a = 2 angle b = 3 angle c >>>More
The area of the first square is the square of (40 4), i.e., 100 square centimeters, and the area of the second square is half the area of the first square, i.e., 1 2, therefore, the area of the sixth square is. >>>More
Iron sheets are needed to find the surface area, and the top and bottom surfaces of the water pipe are empty. >>>More